Contribution of Project Work to Cognitive and Affective Development of Project-Based Learners: Students’ Perspective - Zečević, Snežana M.; Blagojević, Savka N. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
This paper presents the description of projects designed within the project-based learning, as well as the assessment of the students, participants in this type of learning, concerning the contribution of the project work to the students’ cognitive and affective development, that is, to the improvement of their language skills and knowledge and their personal development. The projects were realized by the fourth-year students of the Department of English Language and Literature at the Faculty of Philosophy in Kosovska Mitrovica, while students’ opinions regarding the contribution of project-based learning to their cognitive and affective development were collected by means of a questionnaire. The data were analysed by applying descriptive statistics and the final results proved the hypotheses of the research which emphasized the significance of the project-based learning approach for English language teaching at the tertiary level of education.
Keywords: project-based learning; cognitive and affective development; English language teaching; students of English language and literature